The Effect of Safety Culture and Sense of Belonging on The Performance of Company Employees in Banten During the Covid-19 - Santi Riana Dewi; Rt. Erlina Gentari (Ilomata International Journal of Management, 2021)
During the COVID-19 pandemic, companies experienced changes in working hours and faced different work situations from before the pandemic. One of the most important things to face these challenges is how to maintain the performance of the company's employees so that they continue to give their best performance. This is due to health threats, changes in the work system, and changes in the environmental conditions faced. The novelty of the study when compared with previous studies is that there are differences in exogenous variables. The researcher analyzed the influence of the safety culture and sense of belonging variables on performance, which was processed using SMART PLS to determine the magnitude of the influence of each variable indicator. The research method used is a quantitative method with a survey approach. This study used a sample of 66 people who were obtained by random sampling technique, had a minimum of one year of work experience and were permanent employees of the company. Each variable will be tested for convergent validity, discriminant validity, reliability, R2, and significance. The results of the research based on the value of R2 show that the culture of safety and sense of belonging has an influence of 24.6% on performance. The safety culture indicators have a significant effect on performance with a T count = 4.655, while the sense of belonging has a significant effect on performance with a T count = 3.451. Finally, it can be concluded from the results of research on employees of manufacturing companies in Merak Banten that both latent variables exogenous safety culture (X1) and sense of belonging (X2) with their indicators significantly affect performance (Y). This means that by increasing the culture of safety and sense of belonging, it will be able to improve employee performance in the company.